Women Empowerment in Talent Group Interest Activities at Satya Wacana Christian University - Kristina Roseven Nababan; Kurniawati kurniawati; Rigma Vellanika Shamsahara (Universitas Negeri Medan, 2020)
This research aims to obtain an overview of gender equality in the Talent Group Interest (KBM) activities at Satya Wacana Christian University. This research used a qualitative method, where each data is taken from the observation and interviews with the research subject consisting of the Chairman and members of the KBM existing in the University and the validity technique of data using the triangulation of the source and method. The results found in this study were that gender equality and the opportunities that women had in occupying certain positions existed in each KBM were the same and there was no distinction between women and men, especially in terms of leadership. It is explained that anyone can occupy a specific position with conditions and criteria that have been determined and must be able to be accountable to the KBM. It proves that men and women have the same rights to continue to arise and strive for the sake of the KBM. Besides some of the advantages of the KBM if led by women have the opportunity to be more advanced, because women are seen more thoroughly and more attention to detail matters. The weakness that can arise when it is not possible to decline when women are difficult in determining decisions and need support from other members of both men and women to find the solutions.